Towards openness: A reflection on functional behaviour assessment in schools - Vanderaa, Sonja (Curtin University, 2016)
Drawing on the work of Hans-Georg Gadamer, this study calls into question aspects of functional behaviour assessment’s inheritance from behavioural science. The nature of the inquiry is narrative, autobiographical, reflective, hermeneutical and phenomenological. It asks the question: In what ways might openness to the self, to the other and to the situation, contribute to a more pedagogically sensitive practice of functional assessment in schools? It conceives of openness as an act of resistance.